La taxe fédérale de vente sur les matériaux de construction : quelques simulations avec le modèle CANDIDE 1.1 - Schweitzer, Thomas (L'Actualité économique, 1975)
AbstractThis paper simulates the economy of the period 1963-71 under the assumption that the federal sales tax on construction materials had never been introduced.Evidently, under such circumstances the revenues of the federal government would have been lower than with the construction materials tax in force. We attempted to compensate for the "shortfall" in revenues by raising other taxes or by reducing federal government expenditures.The simulations suggest that the absence of the construction materials sales tax would have led at best to an additional 9,300 housing starts in 1971. Construction costs in 1971 would have been 5%-8.5% lower than actual, depending on the compensatory policy. Somewhat less inflation and somewhat more housing starts can be obtained at the price of lower real growth and higher unemployment. The choice remains, ultimately, a political one.